PENGARUH TEH DAUN KELOR TERHADAP PRODUKSI ASI PADA IBU PASCA BAHAGIA DI KLINIK PRIMER SITI KHOLIJAH HSB - Suyanti Suwardi; Roslina Yulianti; Novy Ramini Harahap; Indah Dewi Sari; Adevia Indah Puri (Jurnal SMART Keperawatan, 2025)
Background: Breast milk is a beneficial substance for baby's growth. Based on the Health Profile of North Sumatra Province in 2022, newborns aged less than 6 months obtained exclusive breastfeeding by (35.96%). During initial surveys at the Siti Kholijah Marelan Primary Clinic, 15 postpartum mothers provided breast milk to their babies, but the milk produced was insufficient. Objective: This study aimed to determine the intensity of smooth breast milk production in postpartum women before and after being consuming moringa tea at. Methods: This is a quasi-experiment with one group pretest and posttest with no control design. Purposive sampling was used to select 10 postpartum women from a population of 25 to consume moringa tea twice a day for 7 days. The color and questions in the ASI production were among the instruments used in the penalty. The production of breast milk in postpartum moms is the dependent variable in this study, whereas the independent variable is the administration of 2 grams of Moringa leaf tea twice daily for seven days, brewed with 150 milliliters of hot water. The data was analyzed using Paired Sample T-tests. Results: obtained the mean value of breast milk production before and after giving moringa tea (14.10-50.50), as well as the standard deviation of breast milk production before and after giving moringa tea (8.252-13.834). The results show that value of 0.001 <0.05, indicating that moringa tea drinking affects the smooth production of breast milk in postpartum mothers.